Cultivo de pacu Piaractus mesopotamicus sob diferentes densidades em tanque-rede no Reservatório de Itaipu - Bittencourt, Fabio (2008)
The aim of this study was to evaluate the management, erythrocytic features and blood glucose level of pacu (Piaractus mesopotamicus), submitted to different stocking densities, cultivated in cages in Itaipu reservoir. The experiment was realized in the transition area of Binational Itaipu in the Research Developing Center of Fish Culture in Cage localized in the Biological Shelter of Santa Helena county, state of Parana, for a period of 240 days. Two thousand and seven fish were used, with initial average weight of 142.11±10.54g distributed in nine cages with sizes of 2.0 x 2.0 x 1.5 m of length, width and height, respectively, totalizing 5 m³ of useful volume, in three different densities, 200, 300 and 400 fish per tank, that is 40, 60 and 80 fish/m³. The experimental delineation was completely randomized compound of three treatments and three replicas. The treatments consisted of three stocking densities. The animals were fed extruded commercial feed containing 32% of crude protein and were fed three times a day until apparent sufficiency. At the end of the experimental period, fish remain in fast for 24 hours, for later collect blood and evaluate the parameters of fulfillment, output and chemical composition of the animal s carcass. No statistic differences (P>0.05) between treatments on the performance average as surviving and feed conversion, but, final weight and weight gain decreased linearly according to the increasing of stocking density. Final biomass increased linearly with the increasing of number of animals stocked per productive unit. The output values of the carcass as pattern length, total weight, eviscerated weight, clean torso, fillet, head, visceral fat and hepatossomatic index did not present significant differences (P>0.05) between the treatments, however, the highest total length (P<0.05) was verified in fish stocked in minor number, not differentiating from those that were cultivated in intermediate density. The chemical analysis of the animal s carcass did not differ statistically (P>0.05) to the variables of dry matter, protein and mineral matter, however, the greatest lipidic deposition was observed in fish cultivated in lower density, not differing from those allotted in intermediate density. The erythrocytics variable like total erythrocytes, hemoglobin and hematocrit did not present statistically differences (P>0.05) for the treatments used and remained in between the normal level to pacu. The glucose tenors did not differ significantly (P<0.05) between the densities analyzed, but presented high values to the species. Stocking densities didn t influenced erythrocytic parameters, fish blood glucose tenor and output of pacu´s carcass. The lowest density provided individuals with higher final weight and weight gain, nevertheless, the productivity per area was reduced and the lipidic deposition was higher